Comparative Evaluation of Various Empirical Methods for Estimating Groundwater Recharge - M. H. Ali; S. Mubarak; M. A. Islam; P. Biswas (Archives of Current Research International, 2017)
Information on groundwater recharge is essential for sustainable groundwater resources management. Estimation of recharge, by any method is normally subject to large uncertainties and errors. In this paper, various empirical methods of estimating natural groundwater recharge were compared with respect to recharge obtained by tracer technique. The comparison results showed that, Chaturvedi Formula, Modified Chaturvedi Formula, and Sehgal formula under-estimated recharge; while other formulas over-estimated. The Chaturvedi Formula under-estimated the greatest amount, while the Maxey-Eakin method over-estimated the greatest amount. The Kirchner et al. formula performed better under the study condition. Modification/adjustment of various equations was also performed based on the tracer results. The modified equations predicted the recharge with good accuracy (mostly <11% relative error). These equations can be used for similar climatic and physiographic conditions, and may be useful for estimating recharge.